Placing an ethical brand: the Fairtrade Towns movement. Issue 15 (13th October 2021) - Peattie, Ken; Samuel, Anthony
ABSTRACT: This study explores the relatively new potential of places to ethically enhance their branding through accreditation under the Fairtrade Towns (FTT) scheme. It presents insights from a qualitative study of marketing practices across eleven UK FTTs, focussing on the activists who establish these initiatives to facilitate and promote FT consumption within their communities. FTT accreditation is revealed as a grassroots local branding initiative that can work symbiotically with the place brand through connections to other fundamental aspects of a place's identity and character, or even by playing a 'redemptive' role. FTT status encourages a less introspective approach to place branding by connecting with distant producer communities and encouraging tourists and residents to reconsider their consumption in the context of the socio-environmental realities of global supply chains.